2002
DOI: 10.1093/humrep/17.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gonadotrophic stimulation on integrin expression in the endometrium

Abstract: As these integrins have been shown to be important in implantation their reduced expression after IVF treatment may have an adverse effect on pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 30 publications
2
18
0
3
Order By: Relevance
“…It has been clinically demonstrated that patients with high E 2 concentrations produce significantly more oocytes and also have elevated progesterone concentrations [22]. Nevertheless, when abnormal steroid hormone concentrations appear, it can be detrimental to endometrial morphology and hence deter receptivity [23]. Alterations in the timing of endometrial development during each menstrual cycle or the quality of endometrial receptivity during the window of implantation are highly implicated in IVF failures [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been clinically demonstrated that patients with high E 2 concentrations produce significantly more oocytes and also have elevated progesterone concentrations [22]. Nevertheless, when abnormal steroid hormone concentrations appear, it can be detrimental to endometrial morphology and hence deter receptivity [23]. Alterations in the timing of endometrial development during each menstrual cycle or the quality of endometrial receptivity during the window of implantation are highly implicated in IVF failures [24].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have indicated an effect of ovarian stimulation on molecular processes involved in implantation. A number of proteins considered to be key regulators in the implantation process, such as integrins (7,8), glycodelin-A (9), and the L-selectin ligand (10), were shown to be differentially expressed in stimulated compared with natural cycles. In recent years, the emergence of microarray technology has enabled the study of the entire gene expression profile of the endometrium and several studies have reported dysregulated gene expression after ovarian stimulation (11,12).…”
mentioning
confidence: 99%
“…Показано, что экспрессия интегрина αvβ3 начиналась в естественном цикле на 7-й день после пика ЛГ, тогда как в циклах с применением ова-риальной стимуляции экспрессия этого фактора адгезии начинается с 5-го дня после назначения ХГЧ, что может го-ворить о смещении «окна имплантации» при стимуляции яичников [39]. Однако несмотря на сообщения об успеш-ном определении интегринов как маркеров имплантации у человека, не все исследователи сообщили о клинической применимости данных методов [40].…”
Section: пиноподииunclassified